Glass ceramics sealants for SOFC interconnects based on a high chromium sinter alloy. Issue 2 (24th October 2017) - Schilm, Jochen; Rost, Axel; Kusnezoff, Mihails; Megel, Stefan; Michaelis, Alexander
Abstract: The operation of solid oxide fuel cells requires gas tight and stable sealing materials. Glass ceramic materials have been established to seal different stack designs and can be optimized to match the requirements of components and joining conditions. It is known that glass‐based sealants are sensitive to the formation of undesired chromia species in contact with ferritic steels used as interconnects. Their formation depends on the earth alkaline type and content in the glass as well as the chromium content of the interconnect. A robust interconnect material is the chromium‐based sinter alloy CFY with >93 wt.% chromium what in turn enforces the formation of chromia phases. SOFC stacks with chromium‐based interconnects and electrolyte supported cells with 10SCSZ electrolyte are candidates for SOFC systems with high efficiency in a wide power range. This study presents results on the development of sealing glasses adapted for the CFY by optimizing the glass components BaO, CaO, SiO2, and Al2 O3 . Depending properties like crystallization behavior, thermal expansion, adhesion and reactivity in contact with CFY have been regarded. The glass has been tested under operating conditions of SOFC (dual atmosphere, electric potentials) in samples as well as in real stacks. It has been shown that optimized glass compositions, especially regarding a limited BaO content combine a good joining behavior and minimized BaCrO4 formation in contact with the CFY alloy.